Sociodemographic and psychological factors associated with depression among nursing home elders - Widyasari, Eka; Ariani, Tutu April; Aini, Nur; Marta, Ollyvia Freeska Dwi; Mashfufa, Erma Wahyu (MEDISAINS: Jurnal Ilmiah Ilmu-Ilmu Kesehatan, 2025)
Introduction: Depression in the elderly is shaped by sociodemographic and psychological factors. Depression generally affects older adults and is associated with a poor life, with sociodemographic and psychological factors such as social support and loneliness playing a role in the onset of depression. However, the relationship between these factors and depression in the elderly is still rarely explored.Purpose: This study aims to explore the relationship between psychological and sociodemographic factors on the level of depression in the elderly living in nursing homes, with a focus on social support, level of loneliness, and cognitive impairment.Methods: This study used a descriptive cross-sectional design and involved 72 older adults living in four East Java, Indonesia nursing homes. Data were collected through questionnaires using the Multidimensional Scale of Perceived Social Support (MSPSS), UCLA Loneliness Scale, Mini-Mental State Examination (MMSE), and Beck Depression Inventory-II (BDI-II), which were translated into Bahasa Indonesia. Multiple logistic regression was used to understand the relationship between sociodemographic and psychological factors and the level of depression in the elderly.Results: Marital status (AOR 0.177, p = 0.030) and social support (AOR 0.950, p = 0.040) are significantly associated with depression in the elderly.Conclusion: Marital status and level of social support have the potential to cause depression in the elderly living in nursing homes.